Ventilation Prior to Umbilical Cord Clamping Improves Cardiovascular Stability and Oxygenation in Preterm Lambs After Exposure to Intrauterine Inflammation - Lio, Alessandra; Aurilia, Claudia; Zahra, Valerie; Moss, Timothy J.; LaRosa, Domenic A.; Hooper, Stuart B.; Gill, Andrew W.; Kluckow, Martin; Nitsos, Ilias; Vento, Giovanni; Polglase, Graeme R. (Frontiers in Pediatrics, 2018)
Background: Delaying umbilical cord clamping until after aeration of the lung (physiological-based cord clamping; PBCC) maintains cardiac output and oxygenation in preterm lambs at birth, however, its efficacy after intrauterine inflammation is not known. Given the high incidence of chorioamnionitis in preterm infants, we investigated whether PBCC conferred any benefits compared to immediate cord clamping (ICC) in preterm lambs exposed antenatally to 7 days of intrauterine inflammation. Methods: Ultrasound guided intraamniotic injection of 20mg Lipopolysaccharide (from E.coli:055:B5) was administered to pregnant ewes at 0.8 gestation. Seven days later, ewes were anaesthetised, preterm fetuses exteriorised via caesarean section, and instrumented for continuous measurement of pulmonary, systemic and cerebral pressures and flows, and systemic and cerebral oxygenation. Lambs were then randomised to either PBCC, whereupon ventilation was initiated and maintained for 3 minutes prior to umbilical cord clamping, or ICC where the umbilical cord was cut and ventilation initiated 30s later. Ventilation was maintained for 30 minutes. Results: ICC caused a rapid fall in systemic (by 25%) and cerebral (by 11%) oxygen saturation in ICC lambs, concurrent with a rapid increase in carotid arterial pressure and heart rate. The overshoot in carotid arterial pressure was sustained in ICC lambs for the first 20 minutes of the study. PBCC maintained cardiac output and prevented the fall in cerebral oxygen delivery at birth. PBCC lambs had lower respiratory compliance and higher respiratory requirements throughout the study. Conclusion: PBCC mitigated the adverse effects of ICC on oxygenation and cardiac output, and therefore could be more beneficial in preterm babies exposed to antenatal inflammation as it maintains cardiac output and oxygen delivery. The increased respiratory requirements require further investigation in this sub-group of preterm infants.